Lecture notes on equilibrium point defects and thermophysical properties of metals - Kraftmakher, Yaakov (World Scientific, 2000)
Includes bibliographical references (p. 303-322) and index; This book discusses the experimental results and theoretical considerations favoring each claim. At present, the majority of the scientific community hold the first viewpoint. Regrettably, the data supporting the second viewpoint have never been displayed and discussed together, and the criticism of this viewpoint has never included a detailed analysis. Important arguments supporting this viewpoint have appeared in the last decade. It may turn out that just calorimetric determinations provide the most reliable values of equilibrium defect concentrations in metals. In this book, the main attention is paid to equilibrium point defects in metals and their relation to thermophysical properties of metals. Along with a discussion on experimental data and theoretical estimates now available, some approaches are proposed that seem to be most suitable for settling the question.